Requirements for microbiological quality management of the agricultural products. Issue 5 (14th September 2015) - Noor, Rashed; Feroz, Farahnaaz
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to portray a general situation on the microbiological spoilage aspects of agriculture and focus on the necessary management schemes of microbiological contamination aiming to deliver information on the public health safety. Design/methodology/approach – A substantial number of local studies on nutritional policies have been performed earlier; however, the microbiological quality control of the agricultural products is still scarce. This review analyzes the microbiological aspects of local agricultural products together with the study findings relevant to food safety as published both globally and locally. Findings – Ongoing awareness on the microbiological quality in accordance to the recommended microbiological limit of different fresh produces would deliver a practical outcome in the safe crop management. Information on microorganisms contaminating agricultural products is expected to ensure public health safety especially within the developing countries along with Bangladesh. Originality/value – The improvements in agriculture status in Bangladesh, particularly in microbiological quality perspective, have been relatively slow, principally due to lack of knowledge on the health risks within the mass population caused by microorganisms harbored through the agricultural products. The novelty of the current review, thus, underlies the necessity of microbiological quality management of the agricultural products, projection on the specific microorganisms contaminating the agricultural products and possible disease outbreaks caused by the consumption of these contaminated products.